2021
DOI: 10.1007/s10490-021-09784-8
|View full text |Cite
|
Sign up to set email alerts
|

Responsible innovation in organisations – unpacking the effects of leader trustworthiness and organizational culture on employee creativity

Abstract: Ongoing changes in competitiveness and advancements in technology are challenging the ability of manufacturing firms to bring about responsible innovation in emerging economies.A crucial response to this situation involves supporting employee creativity as a strategy suited to foster responsible innovation. Prior research has established a positive correlation between employee creativity and responsible innovation. However, when attempting to promote employee creativity, firms are often faced with challenges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 121 publications
1
15
0
Order By: Relevance
“…We review the literature on HR digital transformation resulting from digital disruptions that different authors have popularized by different names at different points in time. The literature has used assorted terminologies, such as digital HRM (Strohmeier, 2020), e-HRM (Prakash, Krishna, & Mores, 2019), sustainable HRM (Agarwal, Mathiyazhagan, Malhotra, & Saikouk, 2021), HR digitalization (Jedynak, Czakon, Kuźniarska, & Mania, 2021), and smart HRM (Ogbeibu, Pereira, & Burgess, 2021) to explain the concept of HRDT, which not only differs in terms of definitions but also lacks conceptual clarity and understanding. In Table 1, we provide the definitions of these terminologies from various studies.…”
Section: Hrdtmentioning
confidence: 99%
“…We review the literature on HR digital transformation resulting from digital disruptions that different authors have popularized by different names at different points in time. The literature has used assorted terminologies, such as digital HRM (Strohmeier, 2020), e-HRM (Prakash, Krishna, & Mores, 2019), sustainable HRM (Agarwal, Mathiyazhagan, Malhotra, & Saikouk, 2021), HR digitalization (Jedynak, Czakon, Kuźniarska, & Mania, 2021), and smart HRM (Ogbeibu, Pereira, & Burgess, 2021) to explain the concept of HRDT, which not only differs in terms of definitions but also lacks conceptual clarity and understanding. In Table 1, we provide the definitions of these terminologies from various studies.…”
Section: Hrdtmentioning
confidence: 99%
“…They assume CDOs to deal with the DT challenges ( [79]) generating new digital solutions, developing new business areas, and evolving existing business models. Furthermore, according to [41], DTs are changing the dynamics of business competitiveness, leading to a rethinking of the levels of responsible innovation driven by the creativity of employees and the organization as a whole. So, in line with the latter literature, this article supports the relevant role of CDOs' capabilities on organizational creativity, especially when organizational creativity promotes responsible innovation processes.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that transformational or transactional leadership styles influence innovation capability. Ogbeibu et al [41] talked about the need of firm direction and leadership as well as interdepedence between a team in an organization and the necessity to be efficiently supported by the appropriate digital capabilities needed to push changes in the organization. Becker et al [79] asserted that the CDO position has been developed to face the aforementioned challenges that occur during a business model undergoing DT.…”
Section: Substantive Capabilities and Digitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alliance learning also provides a means for improving responsible innovation in Asian-market SMEs (Ogbeibu et al, 2021). In this regard, De Marchi et al (2018) suggested that environmental or social issues do not represent the core business of many organizations, which thus often lack the knowledge needed to foster responsible innovation.…”
Section: Sense-making Competencymentioning
confidence: 99%